Non-Muslim dalam Arena Ekonomi Islam: Faktor yang Mempengaruhi Minat Menabung pada Bank Syariah di Langsa Aceh. - Yusaini Yusaini; Ismail Fahmi Arrauf Nasution; Miswari Miswari (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
This article aims to analyze the factors that influence the interest of non-Muslims in Langsa Aceh to save in sharia banks. This study with non-Muslim samples in Langsa Aceh uses field research with a focus on interviews and observations to find data. Furthermore, the data is reduced and processed with rules that have been determined in the field research system. The findings of this study indicate four important factors that influence the interest of non-Muslims in Langsa Aceh to save in sharia banks. First is knowledge factor, second is location factor, third is promotion factor, and fourth is environmental factor. An important recommendation from this research is that sharia banks realize the enthusiasm of non-Muslims to save in sharia banks so that they become a focus of promotion and socialization. Sharia banks must offer an objective system of the advantages of the Islamic banking system.